2020
DOI: 10.1111/jan.14722
|View full text |Cite
|
Sign up to set email alerts
|

Stroke disease‐specific quality of life trajectories after rehabilitation discharge and their sociodemographic and clinical associations: A longitudinal, multicentre study

Abstract: Aim To investigate the longitudinal growth trajectories of disease‐specific quality of life (QoL) dimensions and their associations over 1 year. Design A longitudinal design. Data were collected between February 2015‐May 2017. Methods Four hundred and fifteen stroke survivors (mean age 70.6 years; 81% ischaemic stroke) were recruited after discharge from rehabilitation hospitals and were followed up every 3 months for 1 year. Changes in Stroke Impact Scale (SIS) dimension scores were evaluated using hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…The social participation domain appears to have lower baseline values compared with the cognitive and emotion domains. This finding is consistent with previous studies (Carod-Artal et al, 2009; Chiu et al, 2021; Pucciarelli et al, 2021), although the stroke survivors investigated in those studies were undergoing rehabilitation a year or more post-stroke. Pucciarelli et al (2021) noted a significant linear increase in the SIS domains of stroke survivors discharged from rehabilitation hospitals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The social participation domain appears to have lower baseline values compared with the cognitive and emotion domains. This finding is consistent with previous studies (Carod-Artal et al, 2009; Chiu et al, 2021; Pucciarelli et al, 2021), although the stroke survivors investigated in those studies were undergoing rehabilitation a year or more post-stroke. Pucciarelli et al (2021) noted a significant linear increase in the SIS domains of stroke survivors discharged from rehabilitation hospitals.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies (Carod-Artal et al, 2009; Chiu et al, 2021; Pucciarelli et al, 2021), although the stroke survivors investigated in those studies were undergoing rehabilitation a year or more post-stroke. Pucciarelli et al (2021) noted a significant linear increase in the SIS domains of stroke survivors discharged from rehabilitation hospitals. Our findings also indicated that, among the eight domains of QOL, the three domain of strength, hand function, and social participation had the lowest baseline scores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the whole process, the nurses will discuss to the patients with their profiles and assess their activity level according to the actual situation in order to raise awareness of self-monitoring, self-monitor, and self-efficacy for improving the patient's level of physical activity [ 19 ]. Regarding the emotion dimension, patients in the nursing stage are more aware of the condition and what will happen once relapsing after a period of treatment [ 20 ]. For these reasons, they may follow nurses' suggestions by enhancing confidence and optimistic emotion to improve prognosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the emotion dimension, patients in the nursing stage are more aware of the condition and what will happen once relapsing after a period of treatment [ 20 ]. For these reasons, they may follow nurses' suggestions by enhancing confidence and optimistic emotion to improve prognosis [ 20 ]. As we know, emotional management was important for CVDs, with a vital role for the nurse specialist in terms of counseling and reassurance by focusing on patient activating patients to perform self-management, recovering from depression, may positively influence to change their actions more autonomously [ 15 ].…”
Section: Discussionmentioning
confidence: 99%